Review of Ad Americam Journal of American Studies Vol. 19. - Lénárt, András (AMERICANA E-journal of American Studies in Hungary, 2018)
Ad Americam. Journal of American Studies Vol. 19. Editor-in-chief: Łukasz Wordliczek Institute of American Studies and Polish Diaspora, Jagiellonian University, Krakow, Poland, 2018. 188 pages ISSN: 1896-9461 e-ISSN: 2449-8661